KARAKTERISASI SIFAT FISIK, KIMIA, DAN FUNGSIONAL BAHAN PATI UMBI GEMBILI (Dioscorea esculenta L.) TERMODIFIKASI SECARA IKATAN SILANG DENGAN NATRIUM TRIPOLIFOSFAT - . Herlina (Faculty of Agricultural Technology, University of Jember, 2010)
Gembili starch is one product that potential for wheat flour replacer, and as food additives. However, natural gembili tuber starch has disadvantage that often hinder its application in food processing, such as: the ability to form gels that are not uniform, can not stand on the heating high temperature, the acid conditions, and mechanical process, and susceptible to synerecys . One attempt to exploit the properties of tuber starches gembili is to modify the physical and chemical properties of gembili tuber starch by crosslinking with sodium Tripolyphosphate. The purpose of this study was to determine the physical, chemical and functional properties of gembili modified starch crosslinking using sodium Tripolyphosphate. The experimental design in this study was a randomized block design with 2 factors. Factor A was concentration of sodium Tripolyphosphate (0.05, 0.10 and 0.15% w / w) and factor B was reaction time (30, 60 and 90 minutes). Starch modification resulting tested physical, chemical and functional properties. temperature, viscosity of hot-cold, force expansion, water absorption, texture paste and clarity of pasta. The results showed that the modification of starch by crosslinking with sodium Tripolyphosphate decrease water content, protein, fat, amylose, whiteness, space density, angle of bulk, cold viscosity, water holding capacity, swelling power and paste clarity. However, the modification increased the ash content, gelatinization temperature, hot viscosity, and texture of paste. Testing of starch granules by using Scanning Electron Microscope (SEM) showed that the crosslinking modification process with sodium tripolyphosphate was 0.15% for 90 minutes the starch granules will be more rigid, open, and were amorphous but the shape of granules still survive as a natural condition.Keywords: gembili starch, modification starch, crosslinking modification, functional properties